The Influence of Perceived Convenience, Trust, and Advertising Appeal on Interest in Using Shopeepay on Accounting Students UPN "Veteran" Jawa Timur - Arabela Fidelia Masnal Pabadakayo; Sri Trisnaningsih (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The development of information technology encourages the rapid growth of Financial Technology (FinTech) services, including digital wallets such as ShopeePay. Ease of use, trust, and advertising appeal are the main factors that influence the adoption of this service, especially among students as Generation Z who are known to be adaptive to technology. ShopeePay is one of the popular digital wallets among students, especially accounting students at UPN "Veteran" Jawa Timur. This study aims to analyze the effect of perceived convenience, trust, and advertising attractiveness on interest in using ShopeePay. This research uses quantitative methods with Partial Least Squares (PLS) based Structural Equation Modeling (SEM) analysis techniques. Primary data was collected through an online questionnaire distributed to 78 Accounting students of the 2021 batch of UPN "Veteran" Jawa Timur. The data were analyzed using SmartPLS 4.0 software. The results showed that perceived convenience, trust, and advertising attractiveness had a positive and significant effect on interest in using ShopeePay among students.